TRAFFIC NOISE EXPOSURE AND THE RISK OF HYPERTENSION AND CARDIOVASCULAR DISEASES: A REVIEW - Natalia Kruszewska; Urszula Borucińska; Hanna Pietruszewska; Oliwia Sędziak; Sabina Skrzynecka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Environmental noise originating from road, rail, and air traffic is one of the most significant environmental stressors in urbanized areas. In recent years, growing evidence has indicated that long-term exposure to noise constitutes an independent risk factor for arterial hypertension and cardiovascular diseases. The aim of this review is to provide an in-depth analysis of the biological and social mechanisms underlying these associations, to examine health inequalities related to noise exposure, and to present opportunities for the use of modern noise-monitoring technologies in socio-medical research.Methods: A systematic review of the scientific literature from 2015 to 2025 was conducted, including randomized controlled trials, observational studies, meta-analyses, and reports from the World Health Organization (WHO) and the European Environment Agency (EEA). The review focused on studies assessing the effects of long-term environmental noise exposure on the development of arterial hypertension and the risk of cardiovascular events.Results: Long-term exposure to environmental noise levels exceeding 55 dB significantly increases the risk of hypertension, sleep disturbances, ischemic heart disease, and stroke. The primary pathophysiological mechanisms include activation of the hypothalamic–pituitary–adrenal axis, increased cortisol secretion, oxidative stress, and sleep disruption.Conclusions: Noise is a social determinant of health. Individuals with lower socioeconomic status are more likely to live in areas with high traffic density and poor acoustic insulation, leading to cumulative adverse health effects. In recent years, advanced noise-monitoring technologies such as IoT-based sensors, mobile applications, and geographic information systems (GIS) have been developed to support public health policy. The findings of this review highlight the need for integrated health, environmental, and social strategies aimed at reducing the impact of environmental noise on population health.